John Hejduk, builder of worlds a conversation with David Shapiro - Shapiro, David; Blackwood, Michael; Michael Blackwood Productions (New York, NY : Michael Blackwood Productions, 1991)
Interview with influential architect and teacher, John Hejduk.
Title on container: Hejduk : builder of worlds.
VHS CAN NOT BE CIRCULATED THRU INTERLIBRARY LOAN.
Keywords: Hejduk, John, -- 1929-; Architects -- United States